2016
DOI: 10.1038/srep26563
|View full text |Cite
|
Sign up to set email alerts
|

Protamine zinc insulin combined with sodium selenite improves glycometabolism in the diabetic KKAy mice

Abstract: Long-term, high dosage protamine zinc insulin (PZI) treatments produce adverse reactions. The trace element selenium (Se) is a candidate for the prevention of diabetes due to anti-oxidative stress activity and the regulation of glycometabolism. In this study, we aimed to investigate the anti-diabetic effects of a combination of PZI and Se on type 2 diabetes. Diabetic KKAy mice were randomized into the following groups: model group and groups that were subcutaneously injected with PZI, Se, high or low dose PZI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(45 reference statements)
2
9
0
Order By: Relevance
“…Extracellular SOD3 expression has also been shown to be reduced with the increased production of the superoxide radical (O 2 -•) associated with the decreased expression of the Cu transporter protein ATP7A, in blood vessels from mice with T1DM and T2DM [ 54 ], as well as in patients and those from high-fat-diet-induced T2DM [ 55 ]. In the present study, the increased Zn and Cu levels established by melatonin supplementation in muscle in ZDF rats could also be related to the increased Zn, Cu-SOD activity observed after melatonin supplementation in previous studies [ 17 , 23 , 24 ]. In this regard, melatonin supplementation in these ZDF rats has been shown to lower basal and Fe 2+ /H 2 O 2 -induced plasma lipid peroxidation by improving low-grade inflammation and oxidative stress in this animal model of obesity and T2DM [ 31 ], which could be related to an increase in Zn, Cu-SOD activity in skeletal muscle, which is primarily responsible for the uptake and expenditure of most blood glucose.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Extracellular SOD3 expression has also been shown to be reduced with the increased production of the superoxide radical (O 2 -•) associated with the decreased expression of the Cu transporter protein ATP7A, in blood vessels from mice with T1DM and T2DM [ 54 ], as well as in patients and those from high-fat-diet-induced T2DM [ 55 ]. In the present study, the increased Zn and Cu levels established by melatonin supplementation in muscle in ZDF rats could also be related to the increased Zn, Cu-SOD activity observed after melatonin supplementation in previous studies [ 17 , 23 , 24 ]. In this regard, melatonin supplementation in these ZDF rats has been shown to lower basal and Fe 2+ /H 2 O 2 -induced plasma lipid peroxidation by improving low-grade inflammation and oxidative stress in this animal model of obesity and T2DM [ 31 ], which could be related to an increase in Zn, Cu-SOD activity in skeletal muscle, which is primarily responsible for the uptake and expenditure of most blood glucose.…”
Section: Discussionsupporting
confidence: 76%
“…These researchers [ 15 ] reported that Zn administration stimulated glucose oxidation and glycemic control by modulating the insulin signaling pathway in human and mouse skeletal muscle cell lines. Similarly, Lu et al [ 17 ] demonstrated that protamine Zn insulin combined with sodium selenite improved glycometabolism in T2DM via upregulating phosphatidylinositol 3-kinase (PI3K), downregulating the protein tyrosine phosphatase 1B (PTP1B: Inhibitor of the insulin receptor substrates 1 and 2 [Irs1 and Irs2]), reducing oxidative stress, and ameliorating skeletal muscle and β-cell damage, as well as mitochondrial dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Cd inhibited both aerobic and anaerobic respiration by reducing the expression of glycometabolism-related genes, resulting in apoptosis in chicken spleens. Moreover, Lu reported that sodium selenite improved glycometabolism [ 58 ]. Our results are in support of previous research findings and confirm that Se improves glycometabolism by increasing the expression of LDHA, LDHB, HK1, HK2, PK, SDHB, PFK and ACO2 in chicken spleens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other roles in diabetes mellitus could be attributed to Zn; thus, Zn improved the glycometabolic control in this condition, mediated by the downregulation of the protein tyrosine phosphatase 1B (PTP1B) [ 8 ]. Moreover, Zn inhibited insulin receptor substrates 1 and 2 and consequently reduced oxidative stress [ 9 ] and suppressed ROS generation by its action on the superoxide dismutase enzyme (SOD) [ 10 ]. Copper is another mineral with diverse implications in glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%